Effect of Type and Dates of Canes Taking in Rooting and Growth of Grapevine (Vitis Vinifera L.) Cv. Taifi. - Atrushi, Shawkat M. M.; Nerway, Hussein M. S. (Science Journal of University of Zakho, 2015)
This study was carried out during growing season 2011-2012 on 17 years old Taifi in a private vineyard located near Zawita town, Duhok governorate, Kurdistan region, Iraq, in order to study the effect of type and dates of taking the cutting on rooting and growth of grape transplants, two types of cuttings (basal and middle cutting) were taken at three dates, first at late autumn ( November D1), second at winter (February, D2) and the third at late winter (March, D3), the basal cutting were taken with a part of wood. Results indicated that the basal cutting overtopped in shoot length, No. shoots and leaves per plant, root dry weight and rooting percentage, while never shows it influence on the content of chlorophyll. Whereas first date of taking cutting significantly increased all parameters mentioned above. Interaction of basal cutting + first time of taking had the best significantly values.